2020
DOI: 10.1186/s13148-020-00981-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification mechanisms involved in keloid: current status and prospect

Abstract: Keloid, a common dermal fibroproliferative disorder, is benign skin tumors characterized by the aggressive fibroblasts proliferation and excessive accumulation of extracellular matrix. However, common therapeutic approaches of keloid have limited effectiveness, emphasizing the momentousness of developing innovative mechanisms and therapeutic strategies. Epigenetics, representing the potential link of complex interactions between genetics and external risk factors, is currently under intense scrutiny. Accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 101 publications
1
45
0
Order By: Relevance
“…Multiple studies have shown that keloid‐derived fibroblasts undergo increased proliferation, increased migration and reduced apoptosis 2,25 . In isolated culture cells, we demonstrate that keloid fibroblasts express high levels of YAP/TAZ mRNA and protein compared to normal skin fibroblasts.…”
Section: Discussionmentioning
confidence: 62%
“…Multiple studies have shown that keloid‐derived fibroblasts undergo increased proliferation, increased migration and reduced apoptosis 2,25 . In isolated culture cells, we demonstrate that keloid fibroblasts express high levels of YAP/TAZ mRNA and protein compared to normal skin fibroblasts.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, promoter regulation and gene quantification can also affect the overall expression level of lncRNAs ( 44 , 45 ). Epigenetic regulation of lncRNAs has been suggested to be an important mechanism contributing to tumor progression ( 46 ). Among them, lncRNA expression could be influenced by changes in the methylation level of its promoter or enhancer region, thus promoting the malignant progression of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric analysis showed that ectopic expression of ATF3 significantly reduced the numbers of apoptotic cells compared to that of the control group, while inhibition of ATF3 increased the apoptotic rate of keloid fibroblast cells ( Figure 3 ). In addition, we evaluated the mRNA and protein levels of apoptosis-related genes, including BCL2, Bad, Caspase3 and Caspase9 [ 18 ], in keloid fibroblast cells. Consistently, real-time PCR analysis showed that ATF3 up-regulation significantly promoted BCL2 mRNA and inhibited mRNA levels of Bad, Caspase3 and Caspase9 ( Figure 4(a-d) ) in keloid fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%